Analysis of Leadership Characteristics Expected by Congregation-al Members of Protestant Christian Churches in Bali - I Gede Victor Hernada Hampatra; I Wayan Ruspendi Junaedi; I Gusti Bagus Rai Utama; Gusti Ngurah Joko Adinegara (The Eastasouth Management and Business, 2026)
This study aims to analyze the leadership characteristics expected by members of the Protestant Christian Church in Bali (GKPB) in responding to church service dynamics and the challenges of Bali's multicultural and religious context. This research employs a qualitative approach using observation and in-depth interviews with members of the Daily Synod Council, the Full Synod Council, pastors, and leaders of regional and categorical church organizations (PBKW, PWDK, SKMR, and PP). The findings indicate that congregations expect church leaders to demonstrate spiritual leadership, servant leadership, inclusivity, cultural contextualization, effective communication, and participatory strategic decision-making. Transformational leadership and high integrity are identified as key factors in fostering trust and sustaining church ministry.